Draft genome sequences of 14 Escherichia coli phages isolated from cattle slurry - Smith, R.; O'Hara, M.; Hobman, Jon L.; Millard, A.D. (American Society for Microbiology, 2015)
The diversity of bacteriophages in slurry from dairy cows remains largely unknown. Here, we report the draft genome sequences of 14 bacteriophages isolated from dairy cow slurry using Escherichia coli K-12 MG1655 as a host.